Women's leadership in agrifood systems: Shared vision & learning agenda - Shijagurumayum, Meghajit; Morgan, Miranda; Majumdar, Manisha; Mehrotra, Nini; Rathore, Vidyun; Ravani, Khanjan (2024)
In 2024, experts from across different sectors in India came together to share their respective experiences and insights on women’s leadership in agrifood systems. During this process, participants co-created a collective vision and shared learning agenda with key questions to guide future research efforts. These provide a starting point to all interested stakeholders seeking to contribute individually and collectively to advancing women’s leadership in agrifood systems, in India and beyond.